Conocimientos, actitudes y prácticas sobre cuidados paliativos en internos de enfermería de la zona 5 en el Hospital Alfredo Noboa Montenegro. febrero – junio 2025. - Moreta Velásquez, Geomayra Nashely (2025)
The general objective of this study was to determine the knowledge, attitudes, and practices regarding palliative care among nursing interns from Zone 5 who were practicing at the Alfredo Noboa Montenegro Hospital during the period February–June 2025. The research was conducted using a quantitative, descriptive, cross-sectional, field-based, and non-experimental approach. A structured questionnaire was administered to a population of 68 rotating interns from five public universities in the region. The results showed that, although the majority of interns had received academic training in palliative care, there were significant differences between institutions in terms of conceptual understanding, emotional preparation, and practical application. Students from the State University of Bolívar demonstrated greater theoretical solidity and favorable attitudes, while interns from other universities, such as UNEMI and UPSE, reported limitations in the execution of essential clinical practices, such as pain management, comprehensive assessment, and bereavement support. The conclusions highlight that theoretical training does not always translate into practical skills, and that emotional preparation remains a cross-cutting weakness. An educational and